Posttraumatic Heterotopic Ossification of the Hip. (August 2018) - Behery, Omar A.; Dai, Amos Z.; McLaurin, Toni M.
Abstract : Introduction: Posttraumatic heterotopic ossification (HO) of the hip frequently follows acetabular fracture and hip surgery and can become symptomatic, with significant pain and limited range of motion (ROM). Definitive treatment may require surgical excision, which can result in serious complications if not planned and executed appropriately. Methods: Surgical excision of posttraumatic hip HO requires appropriate indications, preoperative planning, and intraoperative guidance using fluoroscopy to maximize excision of HO and minimize complications. This video presents a case of severe posttraumatic hip HO, indications and technique of surgical excision using fluoroscopic guidance, postoperative protocol, and the patient's clinical follow-up. Results: Surgical excision along with appropriate postoperative HO prophylaxis and immediate mobilization resulted in significant improvement in hip ROM and return to activities of daily living without complications or recurrence. Intraoperative blood loss can be significant and should be appropriately planned for preoperatively. Conclusions: Posttraumatic hip HO can cause significantly limited hip ROM and pain with resulting disability. Surgical excision of posttraumatic hip HO in a preserved hip joint can be successful in restoring hip ROM and function. Appropriate postoperative HO prophylaxis can prevent recurrence. Abstract : Supplemental Digital Content is Available in the Text.